PENGEMBANGAN KOLEKSI, DAN PENERAPAN MANAJEMEN PERPUSTAKAAN PADA PERPUSTAKAAN FISIP UIN RADEN FATAH PALEMBANG - Yuriz, Salsabila Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Writing this article discusses “Development Of Collections and Aplication Of Library Management”. The purpose of this writing is to describe and find out what collections development and the application 0f library management are like. The data sources in this study are primary data sources obtained from one of the librarians at the library and secondary data sources obtained from references, eitheir in the form of journals, articles, and various relevant research results. This research instrument uses interview guidelines and documentation. Methods of data collections using observation, interviews and documentation. That way, researches can conclude that related to development of collections and the application of library management itself has been implemented quite well, and there are also obstacles they face in carrying out the collection development process, one of which is in the procurement of collections, namely on the budget or funds that obtained. With this article,it is hoped that readers can better understand and know about collection development and the application of library management at the FISIP Library of UIN Raden Fatah Palembang.